New technologies and the bottom of the pyramid: a case study in the construction sector - Teixeira de Gouvêa, Diogo Gabriel; Machado, Renan da Silva; Biscaia, Gabriel; Mota da Silva, Marina Pereira; Vieira, Pedro Senna (Retail Management Review, 2023)
Objective: The article proposes an investigation of aspects of the strategy for the Base of the Pyramid, taking Hart’s protocol script as a theoretical reference, and MRV’s strategic movement in the digitization of its business processes in search of improvement in customer service and in the proposition of services, following the trend of society in its technology interaction. Method: Through the case study, this research intends to investigate a contemporary phenomenon starting from its real context, using multiple sources of evidence, including several public sources of information from the organization and other available secondary data. Main Results: MRV promotes a revolution by changing its business model, adopting BoP 2.0 concepts intertwined with the digitization of its processes and the beginning of its digital transformation journey. Relevance/originality: To speed up the digital transformation process, MRV created a startup to make the digital transformation process more agile, expanding its portfolio of traditional businesses, made possible by the digital wave that Brazilian consumers have been identifying with. Theoretical/methodological contributions: The article focused on an analysis of the revision in BoP 2.0 by Hart (2008) in the item “deep dialogue”, because, given the example and initial study unfolded in MRV, there could be the possibility of replacing it with “ omni interaction”, after a closer study, as it is mandatory that organizations serve bottom-of-the-pyramid customers in all available channels, in an integrated and concise way.